An investigation of consumer pear knowledge, consumer preferences and desirable sensory traits to increase pear consumption - Colonna, Anne E. (2024)
The primary objectives of this research were to give a detailed analysis of fresh pear eating quality and consumer appeal. An online consumer survey based out of Portland, Oregon, USA, was disseminated (n=1,940) to understand consumers' motivations for pear consumption. Consumers listed and rated their most preferred attributes of an “ideal” pear. 219 consumers attended one of two in-person, blind-coded taste trials where they sampled either six early season pears (n=107) or six late season pears (n=112) and rated their liking for each. In the consumer survey, respondents were asked in a free-comment (FC) question to list attributes which described their ideal pear; the top three attributes listed were “juicy” (75%), “soft” (63%) and “sweet” (53%). The characteristics that described an “ideal” pear using check-all-that-apply (CATA) questions specific to appearance, flavor and texture were “ripens by changing color”, “sweet” and “good for eating fresh”. When asked to explain how to tell when pears were ripe and ready to eat, only 16% were able to correctly identify, Check the Neck ™ or stem end, for ripeness for most pears. In the consumer sensory evaluation, the pears that were rated highest in overall liking, 'Paragon' (7.46) and 'Bartlett' (7.33), were also rated the highest for juiciness, sweetness and flavor liking. A correspondence analysis (CA) was run on the CATA data from the late season pear consumer sensory evaluations and the pears that exhibit qualities that have the highest mean impact on liking (sweet, fruity, aromatic and juicy) were the 'Paragon', 'Concorde', 'Anjou' and 'Comice'. This research demonstrated that consumers' concepts of what an ideal pear is to them, matched the qualities of the most preferred pears rated at the in person sensory evaluations. More education about pear ripening and storage is needed to help consumers enjoy pears at the peak of ripeness.